Taxonomic Review of Eumenes Latreille, 1802 (Hymenoptera, Vespidae, Eumeninae) from the New World - Grandinete, Yuri Campanholo; Noll, Fernando Barbosa; Carpenter, James (Zootaxa, 2018)
The genus Eumenes Latreille, 1802, from the New World, is revised based on external morphology and male genitalia. New synonymy is proposed as follows: E. aureus Isely, 1917 = E. americanus de Saussure, 1852; E. bollii oregonensis Bequaert, 1838, and E. b. ehrenbergi Zavattari, 1912 = E. bollii Cresson, 1872; E. consobrinus pedalis Fox, 1894 = E. consobrinus de Saussure, 1855; E. crucifera bolliformis Viereck, 1908, E. c. nearcticus de Saussure, 1855 and E. c. stricklandi Bequaert, 1944 = E. crucifera Provancher, 1888; E. smithii belfragei Cresson, 1872 = E. smithii de Saussure, 1852; E. verticalis coloradensis Cresson, 1875, E. v. neoboreus Bequaert, 1944, E. v. tricinctus Isely, 1917 = E. verticalis Say, 1824. Eumenes flavitinctus Bohart, 1950, revised status, is no longer a subspecies of E. crucifera but elevated to specific level. Eumenes brunneus is elevated to the specific level and a new name is proposed because of homonymy, E. bequaerti Grandinete & Carpenter nom. nov. An identification key for all the species of the genus from the New World is provided and the geographical distributions are updated.